Antibody-dependent cell-mediated cytotoxicity (ADCC) in familial myalgic encephalomyelitis/chronic fatigue syndrome (ME/CFS). Issue 4 (1st October 2020) - Sung, Alexander P.; Tang, Jennifer J.-J.; Guglielmo, Michael J.; Smith-Gagen, Julie; Bateman, Lucinda; Navarrete-Galvan, Lydia; Redelman, Doug D.; Hudig, Dorothy
ABSTRACT: Background: Chronic fatigue syndrome (CFS) is an illness of unknown origin that may have familial risks. Low natural killer (NK) lymphocyte activity was proposed as a risk for familial CFS in 1998. Since then, there have been many studies of NK lymphocytes in CFS in general populations but few in familial CFS. Antibody-dependent cell-mediated cytotoxicity (ADCC) by NK lymphocytes helps control viral infections. ADCC is affected by variant CD16A receptors for antibody that are genetically encoded by FCGR3A . Methods: This report characterizes ADCC effector NK cell numbers, ADCC activities, and FCGR3A variants of five families each with 2–5 CFS patients, their family members without CFS and unrelated controls. The patients met the Fukuda diagnostic criteria. We determined: CD16Apositive blood NK cell counts; EC50s for NK cell recognition of antibody; ADCC lytic capacity; FCGR3A alleles encoding CD16A variants, ROC tests for biomarkers, and synergistic risks. Results: CFS patients and their family members had fewer CD16Apositive NK cells, required more antibody, and had ADCC that was lower than the unrelated controls. CFS family members were predominantly genetically CD16A F/F s for the variant with low affinity for antibodies. ROC tests indicated unsuitability of ADCC as a biomarker for CFS because of the low ADCC of family members without CFS. Familial synergistic risk vs. controls was evident for the combination of CD16Apositive NK cell counts with ADCC capacity. Conclusions: Low ADCC may be a risk factor for familial CFS. Furthermore, characterization of familial CFS represents an opportunity to identify pathogenic mechanisms of CFS. GRAPHICAL ABSTRACT: